Miller Family : Still Sal - Henkes, Kevin (New York : Greenwillow Books, an imprint of HarperCollins Publishers, 2024)
When everything goes wrong on Sal's first day of school, her family and friends lovingly remind her that adjusting to change takes time.
Keywords: First day of school -- Juvenile fiction; Schools -- Juvenile fiction; Adjustment (Psychology) -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- Juvenile fiction; First day of school -- Fiction; Schools -- Fiction; Adjustment -- Fiction; Friendship -- Fiction; Family life -- Fiction; Juvenile fiction